2015
DOI: 10.1021/jp511131x
|View full text |Cite
|
Sign up to set email alerts
|

Push or Pull? Proton Responsive Ligand Effects in Rhenium Tricarbonyl CO2 Reduction Catalysts

Abstract: Proton responsive ligands offer control of catalytic reactions through modulation of pH-dependent properties, second coordination sphere stabilization of transition states, or by providing a local proton source for multiproton, multielectron reactions. Two fac-[Re(I)(α-diimine)(CO)3Cl] complexes with α-diimine = 4,4'- (or 6,6'-) dihydroxy-2,2'-bipyridine (4DHBP and 6DHBP) have been prepared and analyzed as electrocatalysts for the reduction of carbon dioxide. Consecutive electrochemical reduction of these comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
125
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(133 citation statements)
references
References 56 publications
8
125
0
Order By: Relevance
“…This new species can be reasonably assigned as a singly‐deprotonated neutral species, [Mn(pdbpy–H + )(CO) 3 ] ( 1 b ), formed by reductive deprotonation of the starting 1 a upon R1. According to this interpretation, the newly formed bands fit well with the spectroscopic data of Re and Mn complexes that contain the 4‐dhbpy ligand (4,4′‐dihydroxy‐2,2′‐bipyridyl), for which a reductive deprotonation mechanism was reported . In particular, a shift in the high‐energy trueν˜ CO band from 2019 to 2012 cm −1 (7 cm −1 redshift) was observed as a result of the transformation of [Re(4‐dhbpy)(CO) 3 Cl] into the singly‐deprotonated complex [Re(4‐dhbpy–H + )(CO) 3 Cl] − (Table S1) .…”
Section: Resultssupporting
confidence: 76%
“…This new species can be reasonably assigned as a singly‐deprotonated neutral species, [Mn(pdbpy–H + )(CO) 3 ] ( 1 b ), formed by reductive deprotonation of the starting 1 a upon R1. According to this interpretation, the newly formed bands fit well with the spectroscopic data of Re and Mn complexes that contain the 4‐dhbpy ligand (4,4′‐dihydroxy‐2,2′‐bipyridyl), for which a reductive deprotonation mechanism was reported . In particular, a shift in the high‐energy trueν˜ CO band from 2019 to 2012 cm −1 (7 cm −1 redshift) was observed as a result of the transformation of [Re(4‐dhbpy)(CO) 3 Cl] into the singly‐deprotonated complex [Re(4‐dhbpy–H + )(CO) 3 Cl] − (Table S1) .…”
Section: Resultssupporting
confidence: 76%
“…These results present similar values than those published by different authors using analogous complexes [72][73][74][75][76][77][78][79][80][81]. Interphase: Pt|1.C1, rhenium oxidations appear at E p 1.51 V, which seems to be electrochemically irreversible, and a second of reversible character at E ½ 1.90 V. On the other hand C2 presents same peaks at E p 1.46 V and E ½ 1.86 V, respectively.…”
supporting
confidence: 89%
“…eletrochemical-chemical mechanism (EEC) (Manbeck et al[73]) with bromide dissociation as the chemical step (v and vii), Scheme 3: Reaction mechanism for C1 and C2 reversible reductions.The kinetic description for L-containing complexes (L is (E)-2((3-amino-pyridin-4-ylimino)-methyl)-4,6-diterbutylphenol ancillary ligand) is quite similar, without the bromide elimination steps. Reduction processes may be assigned to be of the same nature than those described for C1 and C2.…”
mentioning
confidence: 99%
“…S8, ESI †). 41 Regardless, if these reduction processes may be attributed specifically to a particular moiety, by the shape and position of the peaks it seems that the electrochemical reaction follow a typical electrochemical-electrochemical-chemical reaction mechanism (EEC) previously described by Manbeck et al 37 with bromide dissociation as the chemical step: [38][39][40] Other authors, using bpy ligands, have reported the same reduction values with different degrees of reversibility, because the redox potentials for the rhenium complexes depend on the nature of the ligands.…”
Section: View Article Onlinementioning
confidence: 91%
“…S7, ESI †). [34][35][36][37] In C1, rhenium oxidation appears at E p 1.47 V according to the value reported by Hasselmann et al 15 Also, the reversible reduction of deeb is present at E 1/2 À0.94 V, which is more distinguishable in the working window study (Fig. [34][35][36][37] In C1, rhenium oxidation appears at E p 1.47 V according to the value reported by Hasselmann et al 15 Also, the reversible reduction of deeb is present at E 1/2 À0.94 V, which is more distinguishable in the working window study (Fig.…”
Section: View Article Onlinementioning
confidence: 99%